2020
DOI: 10.3390/antiox9111078
|View full text |Cite
|
Sign up to set email alerts
|

ROS and NO Regulation by Melatonin Under Abiotic Stress in Plants

Abstract: Abiotic stress in plants is an increasingly common problem in agriculture, and thus, studies on plant treatments with specific compounds that may help to mitigate these effects have increased in recent years. Melatonin (MET) application and its role in mitigating the negative effects of abiotic stress in plants have become important in the last few years. MET, a derivative of tryptophan, is an important plant-related response molecule involved in the growth, development, and reproduction of plants, and the ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 146 publications
0
41
0
Order By: Relevance
“…We found that salt treatment can induce an increase in the level of endogenous melatonin in cotton seedlings; exogenous application of melatonin can regulate antioxidant enzymes, redox-related genes, glutathione, etc. In order to remove ROS, melatonin can also induce the accumulation of some representative non-enzymatic antioxidants, such as AsA, phenolic compounds, flavonoids and carotenoids ( Pardo-Hernández et al, 2020 ); as a broad-spectrum antioxidant, interacts with ROS and directly eliminates it ( Lins et al, 2012 ); melatonin induced the expression of some hormones (Auxin, ABA, Ethylene, Brassinosteroid, Jasmonic acid) synthesis and signal transduction related genes, and coordinates other hormones in the cotton defense network; melatonin induced the expression of some transcription factors (AP2/ERF-ERF, C2H2, bHLH, WRKY, etc.) to resist salt stress; melatonin induced the expression of genes related to the phosphatidylinositol signaling system and activates some signaling molecules (IP3, DAG, IP6, Ca 2+ ), Phospholipase C (PLC) hydrolyses PtdInsP2 to generate InsP3 and DAG, which can be converted into PA as a signal molecule and PA as a membrane localization signal.…”
Section: Discussionmentioning
confidence: 99%
“…We found that salt treatment can induce an increase in the level of endogenous melatonin in cotton seedlings; exogenous application of melatonin can regulate antioxidant enzymes, redox-related genes, glutathione, etc. In order to remove ROS, melatonin can also induce the accumulation of some representative non-enzymatic antioxidants, such as AsA, phenolic compounds, flavonoids and carotenoids ( Pardo-Hernández et al, 2020 ); as a broad-spectrum antioxidant, interacts with ROS and directly eliminates it ( Lins et al, 2012 ); melatonin induced the expression of some hormones (Auxin, ABA, Ethylene, Brassinosteroid, Jasmonic acid) synthesis and signal transduction related genes, and coordinates other hormones in the cotton defense network; melatonin induced the expression of some transcription factors (AP2/ERF-ERF, C2H2, bHLH, WRKY, etc.) to resist salt stress; melatonin induced the expression of genes related to the phosphatidylinositol signaling system and activates some signaling molecules (IP3, DAG, IP6, Ca 2+ ), Phospholipase C (PLC) hydrolyses PtdInsP2 to generate InsP3 and DAG, which can be converted into PA as a signal molecule and PA as a membrane localization signal.…”
Section: Discussionmentioning
confidence: 99%
“…It can respond to various biotic ( Mandal et al, 2018 ; Zhao et al, 2021 ) and abiotic ( Chen et al, 2017 ; Yao et al, 2020 ) stresses to resist the influence of environmental changes during plant growth and development. The immune response of melatonin in plants requires the participation of many signaling molecules, such as reactive oxygen species (ROS; Pardo-Hernández et al, 2020 ) and Nitric Oxide (NO; Zhu et al, 2019 ), to transmit both intracellular and intercellular signals. In the field of biotic stress, melatonin is involved in plant resistance to numerous fungus ( Moustafa-Farag and Almoneafy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that coordination between melatonin and NO as a signaling molecule performs many actions in plants such as growth and abiotic stress tolerance [186]. Metabolites that are enhanced are carbohydrates such as fructose, galactose, glucose, sucrose, and proline that are important components of osmotic adaptation in abiotic stress response [96].…”
Section: Melatonin Crosstalk With Phytohormones Under Abiotic Stressesmentioning
confidence: 99%
“…Research has shown that coordination between melatonin and NO as a signaling molecule performs many actions in plants such as growth and abiotic stress tolerance [186].…”
Section: Melatonin Crosstalk With Phytohormones Under Abiotic Stressesmentioning
confidence: 99%